2017
DOI: 10.1093/bib/bbx007
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide characterization of lncRNAs in acute myeloid leukemia

Abstract: Long noncoding RNAs (lncRNAs) are a large family of noncoding RNAs that play a critical role in various normal bioprocesses as well as tumorigenesis. However, the expression patterns and biological functions of lncRNAs in acute leukemia have not been well studied. Here, we performed transcriptome-wide lncRNA expression profiling of acute myeloid leukemia (AML) patient samples, along with non-leukemia control hematopoietic samples. We found that lncRNAs were differentially expressed in AML samples relative to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
38
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 34 publications
2
38
0
Order By: Relevance
“…Transfection lncRNA LOC285758 overexpression vector (LOC285758; lnc6180620115353-1-5), negative control (NC; lnc6N0000 002-1-10), miR-204-5p mimics (Mimic; miR10022693- [1][2][3][4][5] and Mimic control (miR01102-1-1) were purchased from RIBOBIO (Guangzhou, China). RNase-free H 2 O (ST876; Beyotime, Shanghai, China) was used to dilute LOC285758, NC, Mimic and Mimic control to 20 lM and was stored at À20°C for later use.…”
Section: Blood Samplesmentioning
confidence: 99%
See 4 more Smart Citations
“…Transfection lncRNA LOC285758 overexpression vector (LOC285758; lnc6180620115353-1-5), negative control (NC; lnc6N0000 002-1-10), miR-204-5p mimics (Mimic; miR10022693- [1][2][3][4][5] and Mimic control (miR01102-1-1) were purchased from RIBOBIO (Guangzhou, China). RNase-free H 2 O (ST876; Beyotime, Shanghai, China) was used to dilute LOC285758, NC, Mimic and Mimic control to 20 lM and was stored at À20°C for later use.…”
Section: Blood Samplesmentioning
confidence: 99%
“…The data also showed that increased LOC285758 expression could effectively suppress the earlier effects of miR-204-5p on AML cells. Our findings suggest that targeting of miR-204-5p by LOC285758 promotes the cell viability and invasion of AML cells, and thus LOC285758 may have potential as a therapeutic target for AML treatment.Acute myeloid leukemia (AML) is the second most common type of leukemia worldwide [1,2]. The latest statistics revealed that the cure rate of AML in the young is 35%, whereas in the aged it is 15% by modern treatment strategies [3].…”
mentioning
confidence: 99%
See 3 more Smart Citations